How to measure financial literacy? - Marc Oliver Rieger (Journal of Risk and Financial Management, 2020)
Financial (il-)literacy and its effects have been studied extensively in recent years. The measurement of this concept is, however, tricky and numerous measurement instruments exist. In this paper, we study the connection between these measures empirically. We find that these measures are often only slightly related and that this is a so-far overlooked empirical problem in this field. As a result of our analysis, we suggest the combination of two measures as the best potential alternative to the existing measures. Finally, we analyze the predictive power of this suggested measure for stock investment decisions.
Keywords: 330; financial literacy; measurement; financial decisions